Manajemen Pariwisata di Pulau Padar, Taman Nasional Komodo, Labuan Bajo - Maria Feninsia Asni Gabur; Made Sukana (JURNAL DESTINASI PARIWISATA, 2020)
Padar Island as one of the main tourist attraction is part of Komodo National Park in Labuan Bajo. Its tourism potential become more in demand compared to Komodo and Rinca Island. The practice of tourism in this Komodo National Park area does not readily claim the management of tourism especially. The focuses of the Office Komodo National Park are conservation and preservation. This study uses primary and secondary data sources with qualitative and quantitative data types. Methods of collecting data through observation, interviews, and documents with the determination of informants using purposive procedure techniques, and use data analysis qualitatively. The result of this study answer three main problems raised, namely the first on the tourism profile of Padar Island relate to the basis of attraction, accessibility, amenities and ancillary. The second is relate to tourism management including demand and supply, the influence of tourism on natural conditions, forms of interaction of tourist with local communities and benefits gained by the community with tourism activities on Padar Island and the third is relate to resource management strategies on Padar Island by parties Komodo National Park. Keywords: Profile, Tourism, Management, Strategy, Resource